2019
DOI: 10.1016/j.vetpar.2019.01.004
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of a novel cathepsin L-like protease from Taenia solium metacestodes for the immunodiagnosis of porcine cysticercosis

Abstract: Porcine cysticercosis is an endemic parasitic disease caused by infection with Taenia solium that is found predominantly in developing countries. In order to aid in the development of simple diagnostic approaches, identification and characterization of potential new antigens for immunodiagnostic purposes is desired. The cysteine protease family has previously been found to have important immunodiagnostic properties. These proteases are expressed as zymogens which contain a signal peptide, pro-peptide, and an a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 33 publications
(40 reference statements)
0
1
0
Order By: Relevance
“…Cathepsin L can participate in nutrient uptake by catabolizing host proteins into absorbable peptides [15], facilitating parasite migration within the host by cleaving host proteins such as fibronectin, laminin and natural collagen [16,17], inactivating host immune defences by cleaving immunoglobulins, and inhibiting Th1-cell immune responses in infected experimental animals, allowing the parasites to evade host immune responses [18]. Cathepsin L has been considered an important target for the prevention of parasitic infections and has been extensively studied in Schistosoma hepatica, Schistosoma mansoni, and Taenia solium, but limited studies have been conducted on T. spiralis cathepsin L [14,19]. A previous study indicated that T. spiralis cathepsin L promotes larval invasion of hosts and is associated with worm development and female fertility [20].…”
Section: Introductionmentioning
confidence: 99%
“…Cathepsin L can participate in nutrient uptake by catabolizing host proteins into absorbable peptides [15], facilitating parasite migration within the host by cleaving host proteins such as fibronectin, laminin and natural collagen [16,17], inactivating host immune defences by cleaving immunoglobulins, and inhibiting Th1-cell immune responses in infected experimental animals, allowing the parasites to evade host immune responses [18]. Cathepsin L has been considered an important target for the prevention of parasitic infections and has been extensively studied in Schistosoma hepatica, Schistosoma mansoni, and Taenia solium, but limited studies have been conducted on T. spiralis cathepsin L [14,19]. A previous study indicated that T. spiralis cathepsin L promotes larval invasion of hosts and is associated with worm development and female fertility [20].…”
Section: Introductionmentioning
confidence: 99%